The Impact of Working Capital Management on Firms Financial Performance: Evidence from Pakistan - Bagh, Tanveer; Nazir, Muhammad Imran; Khan, Muhammad Asif; Khan, Muhammad Atif; Razzaq, Sadaf (International Journal of Economics and Financial Issues, 2016)
The purpose of this study was to empirically explore the impact of working capital management on firms performance of chosen manufacturing firms listed in Karachi Stock Exchange (KSE). The quantitative research methods, correlation matrix and multiple regressions, secondary data and purposive sampling have been worked out. A random sample of 50 listed non-financial companies on Pakistani Stock Market was selected for the period ranging from year 2005 to 2014. The working capital management has been used as an independent variable i.e. inventory turnover (ITO), cash conversion cycle (CCC), average collection period (ACP), and average payment period (APP). The firm performance (FP) has been used as dependent variable i.e. Return on Asset (ROA), Return on Equity (ROE) and Earning per Share (EPS). The results of multiple regression articulated that the APP, ITO and CCC have negative and significant impact on ROA but ACP has positive and significant impact on ROA. While APP has negative significant impact on ROE. The Inventory turnover (ITO) has negative significant impact on EPS while ACP has positive and statistically significant impact on. The study results advocated that the firm performance of selected firms is influenced by working capital management. By validating the findings with previous researchers, this endeavor will contribute to the literature. It will be beneficial to the academic, social and practical deportment. The study findings endowed with deeper insights into working capital management practices and present recommendations that in turn bring improvements in the firm performance of the targeted firms. Keywords: Working capital, working capital management, financial performance, Pakistan JEL Classifications: C10, C30, D73, E37, F65